2004
DOI: 10.1038/sj.onc.1207911
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of EGFR and caveolin-1 in human glioblastoma cells: evidence that tyrosine phosphorylation regulates EGFR association with caveolae

Abstract: Epidermal growth factor receptor (EGFR) amplification and type III mutation (EGFRvIII), associated with constitutive tyrosine kinase activation and high malignancy, are commonly observed in glioblastoma tumors. The association of EGFR and EGFRvIII with caveolins was investigated in human glioblastoma cell lines, U87MG and U87MG-EGFRvIII. Caveolin-1 expression, determined by RT-PCR, real-time quantitative PCR and Western blot, was upregulated in glioblastoma cell lines (two-fold) and tumors (20-300-fold) compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
119
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 42 publications
(48 reference statements)
14
119
0
Order By: Relevance
“…The constitutive TK activity of the EGFRvIII results in the malignant transformation of cells (Han et al, 1996;Nagane et al, 1996;Huang et al, 1997;Antonyak et al, 1998;Montgomery, 2002;Johns et al, 2003;Abulrob et al, 2004;Luwor et al, 2004;Pedersen et al, 2004). In this study, we found that the EGFRvIII is regulated by the Cbl proteins in an identical manner to the WT EGFR.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The constitutive TK activity of the EGFRvIII results in the malignant transformation of cells (Han et al, 1996;Nagane et al, 1996;Huang et al, 1997;Antonyak et al, 1998;Montgomery, 2002;Johns et al, 2003;Abulrob et al, 2004;Luwor et al, 2004;Pedersen et al, 2004). In this study, we found that the EGFRvIII is regulated by the Cbl proteins in an identical manner to the WT EGFR.…”
Section: Discussionsupporting
confidence: 59%
“…Unlike the wild-type (WT) EGFR, the EGFRvIII is unable to bind to EGF or transforming growth factor-α (Ekstrand et al, 1994;Nishikawa et al, 1994;Moscatello et al, 1996) but, instead, it can dimerize spontaneously (Moscatello et al, 1996;Fernandes et al, 2001;Montgomery, 2002). The spontaneous dimerization and ensuing TK activation of the EGFRvIII is necessary to transform cells (Han et al, 1996;Nagane et al, 1996;Huang et al, 1997;Antonyak et al, 1998;O'Rourke et al, 1998;Montgomery, 2002;Johns et al, 2003;Abulrob et al, 2004;Luwor et al, 2004;Pedersen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Caveolin-1 has a scaffolding domain within its NH2-terminal region. Through this domain, caveolin-1 interacts with G-protein -subunits, HRas, Src-family tyrosine kinases, PKC isoforms, EGF-R, Neu, and eNOS and regulates their activities (Razani and Lisanti, 2001;Abulrob et al, 2004;Cao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A caveolin binding motif within the kinase domain of the EGF receptor mediates the interaction of EGF receptor with caveolin-1 (56,57). In human glioblastoma cell lines, EGF receptor rapidly moves out of caveolae domains in response to EGF and then internalizes and degrades via a clathrin-dependent endocytic pathway (56,58,59). In our studies we detected co-localization and biochemical association between the EGF receptor, integrin ␣2, and caveolin-1 without EGF treatment.…”
Section: Activated Egf Receptor Initiates Transient Internalization Ofmentioning
confidence: 99%
“…Recent studies (55,56) have shown that a variety of cell surface receptors, including the EGF receptor, are present in caveolae and lipid rafts. A caveolin binding motif within the kinase domain of the EGF receptor mediates the interaction of EGF receptor with caveolin-1 (56,57).…”
Section: Activated Egf Receptor Initiates Transient Internalization Ofmentioning
confidence: 99%